1983
DOI: 10.1136/sti.59.5.302
|View full text |Cite
|
Sign up to set email alerts
|

Amine content of vaginal fluid from patients with trichomoniasis and gardnerella associated non-specific vaginitis.

Abstract: SUMMARY Amounts of putrescine, cadaverine, and tyramine were measured in vaginal washings from five patients with non-specific vaginitis (NSV) associated with Gardnerella vaginalis, five patients with trichomoniasis, and five healthy controls. Putrescine and cadaverine were present in all but one sample from the infected patients; tyramine was found in four of five samples from the women with NSV and in two of five samples from those with trichomoniasis. The mean cadaverine to putrescine ratio was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…In accord with the findings of Chen et al (3) and of Sanderson et al (16) in their studies of NSV, we found high amounts of putrescine and cadaverine in all our samples from women with BV, but we also found tyramine in all our BV samples, which they did not. We could not analyze histamine by our method, but Chen et al (3) found it in high amounts in some of their NSV samples.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In accord with the findings of Chen et al (3) and of Sanderson et al (16) in their studies of NSV, we found high amounts of putrescine and cadaverine in all our samples from women with BV, but we also found tyramine in all our BV samples, which they did not. We could not analyze histamine by our method, but Chen et al (3) found it in high amounts in some of their NSV samples.…”
Section: Discussionsupporting
confidence: 81%
“…When the concentrations of putrescine, cadaverine, and tyramine were added together, the result was an even higher amine concentration than in any of the samples with BV. This intermediate sample also contained T. vaginalis and, since amines have been reported to occur in the vaginal fluid of women with T. vaginalis (16), the high amine concentration was probably due to this. The second-strongest intermediate sample was obtained from a woman who had recently been treated for BV but did not fulfill the diagnostic criteria for BV according to Nugent. We calculated the amine concentrations in the vaginal fluid, which are expressed as micrograms per gram of vaginal fluid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other female factors, including a higher organism burden in a woman indicated by WM positivity, were not significantly associated with trichomoniasis in the male partner after adjustment for other factors. T. vaginalis is known to produce amine during growth, resulting in an elevated pH [34]. In vitro, the organism grows optimally in an anaerobic environment with pH levels of 6.0-6.3 [35].…”
Section: Discussionmentioning
confidence: 99%